The Effect of Unemployment And Poverty on The Dynamics of Economic Growth In Ambon City (Short-Term And Long-Term Analysis) - Serang, Mohamad Ratmasa; Seleky, Roy; Hiariey, Harvey; Tehuayo , Erlinda (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This study aims to analyze and measure the influence of Unemployment and Poverty on Economic Growth in Ambon City, both in the context of short-term and long-term relationships. Methods: This study uses a quantitative approach with time series data for the period 2009–2023 in Ambon City. The analytical method chosen is the Error Correction Model (ECM), which is effective for testing dynamic relationships between stationary variables in the first differential (I(1)). The dependent variable is Economic Growth (GROWTH), and the independent variables are Unemployment (UNEMP) and Poverty (POVERTY). Key Results (Initial Estimates): All variables are proven to be non-stationary at the level, but stationary in the first differential. Cointegration is found between the variables, confirming the existence of a long-run equilibrium relationship, thus validly applying the ECM model. In the short run, the initial ECM estimation results indicate that: Changes in unemployment (D(UNEMP)) have a negative and significant effect at the 10% level on economic growth. Changes in poverty (D(POVERTY)) also show a negative relationship, although not statistically significant. The Error Correction Coefficient (ECT) in the ECM model indicates the existence of an adjustment mechanism toward long-run equilibrium.  Implications/Novelty: The use of the ECM model provides methodological novelty, enabling richer analysis by separating short-run (annual fluctuations) and long-run (equilibrium relationship) influences, particularly in the context of local policy in Ambon City.